Porphyrins‐Assisted Cocatalyst Engineering with CoOV Bond in BiVO4 Photoanode for Efficient Oxygen Evolution Reaction. Issue 8 (16th January 2023) - Meng, Linxing; Lv, Zunyan; Xu, Weiwei; Tian, Wei; Li, Liang
Abstract: The application of photoelectrochemical (PEC) water splitting is limited by the sluggish surface oxygen evolution reaction (OER) kinetics. OER kinetics can be effectively improved through cocatalyst engineering. However, the tardy transfer process and serious recombination of carriers are the key factors restricting the cocatalyst development. Taking BiVO4 as an example, a Co‐modified heme film rich in large conjugated ring structures is introduced onto the photoanode surface using a solvothermal method. This film functions as an efficient cocatalyst. It considerably reduces the surface overpotential, promotes the transfer of photogenerated holes, and boosts the kinetics of OER by specifically affecting the formation of OOH*. Simultaneously, the formed CoOV bonds induce strong interaction at the photoanode/cocatalyst interfaces, reducing the recombination of photogenerated carriers. Consequently, the onset potential of the optimized photoanode decreases from 0.45 to 0.07 V and the photocurrent density at 1.23 V versus reversible hydrogen electrode boosts to 5.3 mA cm −2 . This work demonstrates a facile strategy for designing cocatalysts to obtain rapid hole transfer capability and reduced carrier recombination for improved PEC performance. Abstract : A simple solvothermal‐assisted process is utilized to introduce large conjugated ring structure‐rich cocatalyst films onto the surface of the BiVO4 photoanode. The covered films act as an efficient cocatalyst, effectively facilitating the transfer of holes, reducing the surface overpotential, and boosting the kinetics of surface oxygen evolution reaction by precisely affecting the forming processes of OOH*.